Effect of tetrodotoxin on the blood activation and the improvement of the heartmuscle circulation of animals - Tu, Le Xuan; Hanh, Vu Van (Academia Journal of Biology, 2015)
Tetrodotoxin increases the blood coagulation time (395”±24.30”) in comparison with the control (289”±31.30”). Beside, tetrodotoxin attenuates the bleeding time (234”±53.67”) in comparison with the control (333”±70.82”) and also attenuates the haemolysis time (348”±26.43”) in comparison with the control (108”±20.39”). Tetrodotoxin has effect on the bloodfibre disperse, but it has not effect on the erythrocyte cell dispersion and the erythrocyte cell structure. Tetrodotoxin has the ability to recuperate the heart rhythm to the initial stage (202.22±13.07) when the infarct was caused by pituitrin (202.22±13.67). Tetrodotoxin has the ability to recuperate some figures: R, ST, QT of E.C.G at D2 and V1 to the initial stage when the infarct was caused by pituitrin.